2010
DOI: 10.1007/s12039-010-0076-x
|View full text |Cite
|
Sign up to set email alerts
|

Directed 2-dimensional organisation of collagen: Role of cross-linking and denaturing agents

Abstract: The effect of additives like curcumin and surfactants on the self-assembly of collagen from a simple 2-dimensional system of Langmuir films of the protein at air/solution interface has been attempted in this study using quartz crystal microbalance (QCM) and dynamic surface tensiometer. Though pure curcumin is not surface active, a synergistic effect of collagen with curcumin seems to lead to enhanced surface activity in the protein. In general, the presence of additives, increases the surface activity of colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Morphology and aggregation of α-helical protein fibers results from an energetically favorable balance between the burial of the hydrophobic residues and the solvation of the surface-facing polar groups. 56 Our CD studies have confirmed that increasing molar ratios of curcumin affects only helical packing, not protein conformation. Curcumin increases the surface activity of collagen as a result of local restructuring of water, leading to some exposure of nonpolar groups.…”
Section: ■ Results and Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Morphology and aggregation of α-helical protein fibers results from an energetically favorable balance between the burial of the hydrophobic residues and the solvation of the surface-facing polar groups. 56 Our CD studies have confirmed that increasing molar ratios of curcumin affects only helical packing, not protein conformation. Curcumin increases the surface activity of collagen as a result of local restructuring of water, leading to some exposure of nonpolar groups.…”
Section: ■ Results and Discussionsupporting
confidence: 64%
“…With curcumin being fully protonated at pH 4, the interaction of curcumin with negative charges on the protein is likely. 56 Indeed, as curcumin concentration increases, the zeta potential exhibits a slight increase as well, indicating a neutralization of any negative charges through binding to curcumin (Figure 4a). For Q, zeta potential in the absence of curcumin is 19.1 ± 2.5 mV, with a steady increase up to a maximum value of 25.2 ± 0.8 mV at a curcumin concentration of 40 μM (Figure 4a).…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The relatively stiff collagen molecules can self-assemble at the level of microfibrils, fibrils, and suprafibrillar networks [20]. Moreover, solutions of the filament-shaped protein exhibit a lyotropic LC behavior, that undergoes a spontaneous phase transition from isotropic to crystalline state with increasing concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Porous scaffolds are gaining importance in tissue engineering applications and organ regeneration. Collagen, a significant component of the extracellular matrix (ECM), provides principal structural and mechanical support to the connective tissues [3].…”
Section: Introductionmentioning
confidence: 99%